The Content Marketing Analysis on Indonesian Local Brand Fashion on Instagram - Erwita, Monica Adjeng; Handayani, Yuliasti Ika (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2022)
The purpose of this paper is to analyze digital marketing strategy on Instagram among local brand fashion in Indonesia by assessing the content marketing and consumer engagement to build competitive advantages. This research is using content analysis method. A content analysis of 196 social media posts was conducted from the Instagram accounts of 2 local brand fashions in Indonesia during two months between December 2020 and January 2021. The data collected from each social media post generated by those brands were coded and analyzed in terms of their marketing content and consumer engagement. This research found that brand, product information, photo, and consumer appreciation were frequently appearing and effective for informative marketing content. Meanwhile, conversations about brand and product which are consist of quality, emotion, relations, and services were the frequently appearing topics in the comment column and its effective for consumer engagement. Penelitian ini bertujuan untuk menganalisis strategi digital marketing Instagram di kalangan brand fashion lokal di Indonesia dengan mengkaji content marketing dan consumer engagement untuk membangun keunggulan bersaing. Penelitian ini menggunakan metode analisis isi. Peneliit melakukan analisis konten terhadap 196 postingan media sosial dilakukan dari akun Instagram 2 merek fashion lokal di Indonesia selama dua bulan antara Desember 2020 dan Januari 2021. Data yang dikumpulkan dari setiap postingan media sosial yang dihasilkan oleh merek-merek tersebut diberi kode dan dianalisis dalam bentuk konten pemasaran dan keterlibatan konsumen mereka. Penelitian ini menemukan bahwa merek, informasi produk, foto, dan apresiasi konsumen sering muncul dan efektif untuk konten pemasaran yang informatif. Sedangkan perbincangan tentang merek dan produk yang terdiri dari kualitas, emosi, relasi, dan layanan menjadi topik yang sering muncul di kolom komentar dan efektif untuk keterlibatan konsumen. Tulisan ini memiliki keterbatasan, hanya terfokus pada Instagram.